An experimental study on thermal efficiency of hybrid GO/MWCNTs nanoparticles suspended in a binary mixture of ethylene glycol and water. (2023) - Vaka, Mahesh; Walvekar, Rashmi
Graphical abstract: Abstract: Energy consumption has a demand growth across the globe due to modernization. However, the use of fossil fuels is creating a huge impact on climate change and has made it essential to harvest solar renewable energy technology. The heat transfer fluid plays an important role in maintaining the optimum temperature of the panel by removing the heat absorbed and transferring to the thermal energy storage medium. Due to the poor thermal conductivity and thermal degradation of conventional heat transfer fluids such as water, ethylene glycol and oil, these pose limitations to be utilised in solar energy technology systems. Thus, to overcome this problem, a hybrid nanofluid is used to boost the thermal conductivity and degradation temperature. However, the addition of hybrid nanoparticles further enhances the thermo-physical properties of the fluids. In this present study, GO/MWCNTs hybrid nanoparticles (0.01 – 0.2 wt%) were dispersed in hybrid base fluid (EG/water) in the ratio of 40:60. The finding shows that for visual stability, MWCNT sediment was faster compared to GO while, hybrid GO/MWCNT, showed higher stability compared to the single nanoparticle. The TGA results show the higher thermal degradation temperature at 0.05 wt% of pure GO, pure MWCNT and hybrid GO/MWCNT with thermal degradation of 122.74 ℃, 118.93 ℃ and 119.26 ℃ respectively. The use of nanofluids acts as a clean fuel for electricity production and decreases CO2 emission, which can further promote sustainable development goals.